Peran pendidikan moderisasi beragama di perguruan tinggi islam: Studi kasus UIN Sunan Kalijaga, UIN Maulana Malik Ibrahim dan UIN Sultan Maulana Hasanuddin - Husna, Celia Laila (Maliki Interdisciplinary Journal, 2026)
Religious moderation has become a strategic issue in the development of Islamic higher education in Indonesia as a response to growing intolerance, radicalism, and social polarization within a multicultural society. Islamic higher education institutions play an important role in instilling values of tolerance, justice, and respect for diversity among students. This study aims to analyze the implementation of religious moderation education at three state Islamic universities: UIN Sunan Kalijaga Yogyakarta, UIN Maulana Malik Ibrahim Malang, and UIN Sultan Maulana Hasanuddin Banten. The research employs a qualitative method with a library research approach through the analysis of academic literature and institutional documents. The findings reveal that each university applies different strategies in internalizing the values of religious moderation. UIN Sunan Kalijaga emphasizes multicultural education and interfaith dialogue, UIN Maulana Malik Ibrahim focuses on character integration and strengthening lecturers’ roles, while UIN Sultan Maulana Hasanuddin applies a constructivist approach in Islamic education learning. However, implementation still faces several obstacles, including resistance from some academic communities, limited lecturer competence, and uneven institutional policies. This study confirms the importance of curriculum strengthening, lecturer training, and inter-campus collaboration in building a moderate, inclusive, and sustainable Islamic higher education ecosystem.